Descrição morfológica da ontogenia de Hippocampus reidi Ginsburg, 1933 (Teleostei, Syngnathidae): período embrionário à fase reprodutiva - Pontes, Júlia Roberta Sá (2010)
Ontogenetic studies constitute an important step to increase the knowledgebase about shifts in food preference and micro-habitats, as well as for improving taxonomy, production for aquaculture, and fisheries management; they may also shed new light on the implications of the extraction of a high volume of animals for trade. This study aimed to estimate the initial growth of the seahorse Hippocampus reidi, and to morphologically describe its ontogeny, from the embryonic period to the reproductive phase. Both aspects are relevant in face of (1) the morphological and biological singularities of the genus, including the ability to bend the body and the body covering formed by bony rings, a prehensile tail and the development of a pouch in males and (2) the need to increase our understanding of the biology and ecology of seahorses, a group globally threatened by overfishing and habitat loss. Growth was estimated using ex-situ data obtained from two different broods of H. reidi, while description of the ontogeny was done using data collected both in-situ and ex situ. Data were grouped into two distinct phases: planktonic and postplanktonic (when juveniles are able to use holdfasts). The main results obtained in the study are: H. reidi exhibited an initial daily growth rate of 0.017 cm; juveniles showed a decrease in the percentage of the head, and in the depth of the snout and trunk in relation to standard length with age. During the planktonic phase, juveniles exhibited a a positive growth in the tail region, weak pigmentation and had the pectoral fins positioned near the base of the head. After that period, the body acquired a more solid structure, and various base became evident (at 2.59 cm); the snout became more elongated, and the pectoral fins were positioned near the level of the orbits.